Clathrin dependence of synaptic-vesicle formation at the Drosophila neuromuscular junction. - Heerssen, H.; Fetter, R.D.; Davis, G.W. (Current Biology, 2008)
Among the most prominent molecular constituents of a recycling synaptic vesicle is the clathrin triskelion, composed of clathrin light chain (Clc) and clathrin heavy chain (Chc). Remarkably, it remains unknown whether clathrin is strictly necessary for the stimulus-dependent re-formation of a synaptic vesicle and, conversely, whether clathrin-independent vesicle endocytosis exists at the neuronal synapse.We employ FlAsH-FALI-mediated protein photoinactivation to rapidly (3 min) and specifically disrupt Clc function at the Drosophila neuromuscular junction. We first demonstrate that Clc photoinactivation does not impair synaptic-vesicle fusion. We then provide electrophysiological and ultrastructural evidence that synaptic vesicles, once fused with the plasma membrane, cannot be re-formed after Clc photoinactivation. Finally, we demonstrate that stimulus-dependent membrane internalization occurs after Clc photoinactivation. However, newly internalized membrane fails to resolve into synaptic vesicles. Rather, newly internalized membrane forms large and extensive internal-membrane compartments that are never observed at a wild-type synapse.We make three major conclusions. (1) FlAsH-FALI-mediated protein photoinactivation rapidly and specifically disrupts Clc function with no effect on synaptic-vesicle fusion. (2) Synaptic-vesicle re-formation does not occur after Clc photoinactivation. By extension, clathrin-independent "kiss-and-run" endocytosis does not sustain synaptic transmission during a stimulus train at this synapse. (3) Stimulus-dependent, clathrin-independent membrane internalization exists at this synapse, but it is unable to generate fusion-competent, small-diameter synaptic vesicles.